2010
DOI: 10.1108/13552551011027020
|View full text |Cite
|
Sign up to set email alerts
|

Explaining entrepreneurial intentions in the Caribbean

Abstract: PurposeThe purpose of the paper is to highlight the need for Caribbean scholarship to advance and test social psychological models that speak to current entrepreneurial realities on the ground which have implications for theory, education, practice and public policy. It tests a revised entrepreneurial intentions‐based model by examining the impact of several socio‐cognitive predictors.Design/methodology/approachUsing a structural equation modelling approach, a revised model of entrepreneurial intentions is tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 38 publications
0
50
0
11
Order By: Relevance
“…Many scholars have indicated that understanding the relevant contextual factors can provide insights into the nature and dimensions of entrepreneurial climate in a country (Devonish et al, 2010). This study proposes that perceived situation will affect and influence the motivation to study entrepreneurship and consequently form the conviction to start a new business.…”
Section: Psychometric Variablesmentioning
confidence: 99%
“…Many scholars have indicated that understanding the relevant contextual factors can provide insights into the nature and dimensions of entrepreneurial climate in a country (Devonish et al, 2010). This study proposes that perceived situation will affect and influence the motivation to study entrepreneurship and consequently form the conviction to start a new business.…”
Section: Psychometric Variablesmentioning
confidence: 99%
“…The analysis of entrepreneurial intent is the key to explain the process of creation of companies (Devonish et al 2010;Liñán y Fayolle 2015) this is why various studies have sought to identify the key factors affecting individuals regarding the decision to start up a Company (Liñan et al 2005;Obschonka and Rodermund 2010;Valencia, Montoya and Montoya, 2016). These studies have been focused on aspects ranging from the determination of behavioral theories that leads a person to make decisions (Boissin et al 2011;Ferreira et al 2012) to the formulation of models describing the relationships and associations between factors affecting the entrepreneurial intent of individuals (Lanero et al 2014;Hui-Chen et al2014).…”
Section: Analysis Of Entrepreneurial Intentmentioning
confidence: 99%
“…Entrepreneurship can be a sustainable tool for the economic development of the Caribbean [13] and yet there is a lack of entrepreneurial culture in the Caribbean [14] partly due to: the effect of colonialism and slavery [14]; the difficulty of accessing capital to fund new business start-ups; limited entrepreneurship training; limited tax benefits; highly bureaucratic procedures associated with starting a business; deficiencies in the micro financing sector; weak support from the black community and family [14].…”
Section: Entrepreneurship In the Caribbeanmentioning
confidence: 99%